The influence of workplace bullying on the performance of hotel employees: the mediating role of emotional intelligence and psychological resilience - Kamal Adewole Odunjo-Saka; Banji Rildwan Olaleye; Eric Sarpong; Abdurrashid Ibrahim; Jonathan Olusegun Adedokun (Tourism & Management Studies)
Workplace bullying has consistently been observed to have negative impacts on employee well-being by researchers. In the field of bullying research, there hasn't been a study that integrates mediators and explains the nexus between the many different factors that have been studied. Therefore, this study aimed to determine the impact of bullying on workers' performance at hotels in North Cyprus and the mediating role played by emotional intelligence and psychological resilience. Data were randomly collected from 442 hotel employees, including those from five- and four-star hotels on the island. The data were analysed using descriptive analysis. Furthermore, the heuristic model was tested using partial least squares structural equation modelling (PLS-SEM). According to the results, workplace bullying significantly and negatively influences an employee's performance. Secondly, emotional intelligence and psychological resilience positively mediated the relationship between bullying and performance among TRNC hotel employees. More cross-cultural and longitudinal research is needed to determine if these mediators have an enduring effect over time and across different cultures.